Power System Stability Analysis of SMIB with FOPID using Cuckoo Search Optimized Differential Evaluation - M. Gajare, Atul; R. P. Singh, Dr; M. U. Nemade, Dr (International Journal of Engineering and Technology, 2018)
Due to complexity in the power system there is always a loss of the stability due to the fault. Whenever a fault is intercepted in system, the whole system goes to severe transients. These transients cause oscillation in phase angle which leads poor power quality. The nature of oscillation is increasing instead being sustained, which leads system failure in form of generator damage. To reduce and eliminate the unstable oscillations one needs to use a stabilizer which can generate a perfect compensatory signal in order to minimize the harmonics generated due to instability.This paper presents a Power System stabilizer to reduce oscillations due to small signal disturbance. Additionally, a hybrid approach is proposed using FOPID stabilizer with the PSS connected SMIB. Cuckoo Search (CS) Optimized Differential Evaluation (DE) approach is used for the parameter tuning of the stabilizer. The efficiency of proposed approach is observed by rotor angle and power angle deviations in the SMIB system.Â Â